Policy, national regulation, and international standards for GM foods - Phillips, Peter W. B. (International Food Policy Research Institute, 2003)
The introduction of biotechnology into the agri-food world in the 1990s complicated an already difficult regulatory and trade system. At one level, biotechnology and genetically modified (GM) foods increase the potential for trade and the need for a fully functioning international trading system. At another level, the products of this new technology have precipitated a large and difficult debate about the structure and effectiveness of national food safety regulations and the appropriate role for international institutions. A number of national and international efforts are underway to manage these pressures, but prospects for early resolution are not great.